Exploring Alternatives for Sustainable Development of Mixed Vegetable Beef-cattle Family Farm Systems in Southern Uruguay - Aguerre, Verónica; Chilibroste, Pablo; Casagrande, Marion; Dogliotti, Santiago (Agrociencia Uruguay, 2022)
Sustainability of most vegetable family farms in Southern Uruguay is threatened by low income and the deterioration of natural resources. This study quantified the effect of the inclusion of different alternatives of livestock production in the structure, and economic and environmental performance of different types of vegetable farms. Based on two farms as case studies, we conducted a model based exploratory study at farm scale. The results suggested that the inclusion of livestock production in vegetable family farms is a key factor in reducing erosion of the cultivated area. To reduce erosion, the model reduced the area of vegetables per farm, while expanding the area of forage production. As a consequence, family farm income (IF) was reduced between 12 % and 31 % depending on the case studied. However, we could design production systems with erosion lower than the tolerance limit for the soil type and higher IF, relative to the target, in both farms. From the livestock production alternatives evaluated, the most appropriate ones to include in vegetable production systems are fattening steers or heifers in cycles of 14 to 18 months, due to lower cost for restocking and less use of concentrates, reducing capital requirements and dependence on external inputs.